The burden of congenital rubella syndrome in the Philippines: results from a retrospective assessment - Lopez, Anna Lena; Raguindin, Peter Francis; Del Rosario, Jose Jonas; Najarro, Ramon V.; Du, Eleanor; Aldaba, Josephine; Salonga, Aida M.; Monzon-Pajarillo, Andrea Kristina; Santiago, Alvina Pauline; Ou, Alan C.; Ducusin, Maria Joyce (Western Pacific Surveillance and Response, 2017)
Introduction: In line with the regional aim of eliminating rubella and congenital rubella syndrome (CRS), the Philippines introduced rubella-containing vaccines (RCV) in the national routine immunization program in 2010. We attempted to estimate the burden of CRS in the country prior to nationwide programmatic use.Methods: We performed a retrospective chart review in four tertiary hospitals. Children born between January 1, 2009 and December 31, 2014 identified as possible CRS cases based on the presence of one or more potential manifestations of CRS documented in hospital or clinic charts were reviewed.  Laboratory-confirmed cases meeting the clinical case definition of CRS were confirmed CRS cases.  Cases that met the clinical case definition of CRS but without laboratory confirmation were considered as probable CRS cases.Results: We identified 18 confirmed and 201 probable cases in this review. Depending on the hospital, the estimated incidence of CRS ranged from 30 to 233 cases per 100,000 live births. The estimated national burden of CRS was 20-31 cases per 100,000 annually.Discussion: This is the first attempt to assess the national CRS burden.  Prospective surveillance for CRS and further strengthening of the ongoing measles-rubella surveillance are necessary to establish accurate estimates of the burden of CRS and the impact of programmatic RCV use in the future.